Influence of test size, water depth, and ecology on Mg/Ca, Sr/Ca, δ18O and δ13C in nine modern species of planktic foraminifer - O. Friedrich; R. Schiebel; P.A. Wilson; S. Weldeab; C.J. Beer; M.J. Cooper; J. Fiebig (Earth and Planetary Science Letters, 2012)
Mg/Ca palaeothermometry in foraminiferal calcite is a widely applied tool in palaeoceanography. However, our understanding of the effects of planktic foraminiferal ecology and early diagenesis on test calcite Mg/Ca is limited. Here we report results of a study designed to shed new light on ecological, size-related and very early (water column) diagenetic controls on Mg/Ca in planktic foraminiferal calcite. We analysed Mg/Ca and stable isotopes of nine modern planktic foraminiferal species across fourteen mostly 50 μm-window sieve fractions in a core-top sample from the North Atlantic Ocean. We also analysed Mg/Ca in four of these nine species from plankton-tow samples collected from 0 to 2500 m water depth in the North Atlantic Ocean and Arabian Sea. Our core-top study confirms that sensitivity of Mg/Ca to change in test size is species-specific but reveals an overall decrease in Mg/Ca with increasing test size in all but one species, Orbulina universa, for which Mg/Ca increases with size. These findings are broadly consistent with known ecological behaviour suggesting that the size-related signal is largely environmentally rather than calcification-rate controlled. Our results underscore the need to undertake Mg/Ca palaeothermometry on narrow size fractions of planktic foraminifers, particularly for shallow-dwelling species such as G. bulloides and G. ruber where Mg/Ca is most sensitive to test size across the size range of 200–350 μm. Our plankton-tow data from the Arabian Sea are in agreement with in-situ temperatures. In contrast, our data from the North Atlantic Ocean reveal large variability and marked offsets (to warmer values) from in-situ temperatures that are interpreted to reflect lateral advection from the south, storm-induced vertical mixing of the water column and/or the influence of surface-water salinity on the Mg/Ca signal. None of our plankton-tow Mg/Ca data shows any evidence of test dissolution in the water column. Our study provides important verification that the Mg/Ca signal recorded during calcification does not undergo diagenetic degradation during test transport to the sea floor, thereby satisfying an important precondition of its palaeo-proxy utility.